1970
DOI: 10.1111/j.2042-3306.1970.tb04180.x
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Relate Bovine Papilloma Virus to the Cause of Equine Sarcoid: Horses, Donkeys and Calves Inoculated with Equine Sarcoid Extracts

Abstract: Summary Attempts to produce equine sarcoids in horses and warts in calves with extracts of equine sarcoids were unsuccessful. The horses and calves were later demonstrated to be susceptible to bovine papilloma virus (BPV). Tumours were produced in 2 of 5 donkeys 5 to 10 months after inoculation with extracts of equine sarcoids. This was a longer interval than has been observed for tumour formation by BPV. The tumours did not histologically resemble equine sarcoids or BPV‐produced tumours of equine skin. Résumé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 3 publications
1
50
0
2
Order By: Relevance
“…In the case of equine sarcoids, although BPV DNA has been detected widely and mRNA expression for L1 has been shown , there is little evidence for expression of the BPV structural proteins or for virus capsid formation (Reid, 1992). This is supported by the observation that experimental inoculation of sarcoid extracts in cattle does not induce warts (Ragland & Spencer, 1969). Therefore, BPV infection of equine fibroblasts appears to be non-productive.…”
Section: Bpv and The Pathogenesis Of Equine Sarcoidssupporting
confidence: 69%
See 2 more Smart Citations
“…In the case of equine sarcoids, although BPV DNA has been detected widely and mRNA expression for L1 has been shown , there is little evidence for expression of the BPV structural proteins or for virus capsid formation (Reid, 1992). This is supported by the observation that experimental inoculation of sarcoid extracts in cattle does not induce warts (Ragland & Spencer, 1969). Therefore, BPV infection of equine fibroblasts appears to be non-productive.…”
Section: Bpv and The Pathogenesis Of Equine Sarcoidssupporting
confidence: 69%
“…Subsequently, more substantial evidence was provided by transmission studies in which inoculation with either sarcoid tissue or cell-free supernatant from minced tumours onto the scarified skin of sarcoid-free horses resulted in the appearance of tumours at the inoculation site; these sarcoids were morphologically indistinguishable from naturally occurring sarcoids (Voss, 1969). Similarly, inoculation with bovine papillomavirus (BPV) in nonaffected horses resulted in the growth of sarcoid-like tumours (Olson & Cook, 1951;Ragland & Spencer, 1969). However, the artificially induced sarcoids showed spontaneous regression, which is rarely encountered in naturally occurring sarcoid tumours.…”
Section: Evidence For Virus Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,17,22,23,25 Studies have demonstrated the location of BPV in sarcoids using in situ hybridization, 14,25 but while this technique allows for the visualization of BPV, it does not amplify the BPV genome to any significant degree when compared to PCR and is, therefore, a much less sensitive technique for identification of DNA when it is present in small quantities. 17 Laser microdissection (LM) allows for the very precise excision of a cell or cells from a sample of interest.…”
Section: Introductionmentioning
confidence: 99%
“…26,29,34 In subsequent work, Southern blots were used to identify BPV1 or BPV2 genome(s) within tumor tissue, 1,2,19,38 and polymerase chain reaction (PCR)-based surveys routinely demonstrate that up to 100% of sarcoids contain BPV DNA. [12][13][14]23,24,27,38,39 A limited number of studies have been designed to investigate the role of BPV in cellular transformation in equine tissue.…”
mentioning
confidence: 99%